Informational Quality of Financial Systems and Economic Development: An Indicators Approach for East Asia - James H. Chan-Lee; Sanghoon Ahn (Asian Development Bank Institute (ADBI), 2001)
In this ground-breaking study, over 50 countries, including emerging market economies (EMEs) and OECD, are examined for the informational quality of their financial systems using nearly 30 microeconomic and institutional indicators. By assessing recent institutional and structural reforms against a statistical benchmark, the findings suggest disproportionate gains occur in per capita GDP with improvements in the social infrastructure. The authors also find that better enforcement of law is more important than the origins of legal systems. This new indicator could be used to make more transparent and insightful strategic diagnoses of EMEs' financial systems and to assess and compare systemic risks.
hdl:11540/4125
Keywords: 330